FRAMING ANALYSIS IN THE NEWS OF THE SEXUAL HARASSMENT CASE OF JUNIOR HIGH SCHOOL STUDENTS IN LANGKAT ON ONLINE MEDIA CNNINDONESIA.COM - Syafruddin Pohan; Sinta Azhary Ginting; Syifa Urrahmah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research aims to analyze the framing in the news coverage of the sexual violence case against a junior high school student in Langkat, North Sumatra using a case study of the CNN Indonesia news portal. This research was conducted to understand how the media, in this case CNN Indonesia, framed the case through the presentation of news and the point of view used in the reporting. The research method used is descriptive qualitative method, with a focus on framing analysis. This research aims to explore and understand the meaning given by individuals or groups to the social issues discussed. The research data was obtained from CNN Indonesia's online media platform. The data consists of news articles related to cases of sexual violence against junior high school students in Langkat, North Sumatra. Data collection techniques involved collecting information from CNN Indonesia's online portal, reading and identifying information and ideas in the selected news articles, analyzing the news using the framing analysis model of Zhongdang Pan and Gerald M. Kosicki, presenting the results of the analysis, and drawing conclusions.